Handgrip and quadriceps muscle endurance testing in young adults - White, C.; Dixon, K.; Samuel, D.; Stokes, M. (SpringerPlus, 2013)
Background: Grip strength is widely used for estimating whole body strength but there is a lack of information relating to grip endurance. Comparison between endurance of different muscle groups has received little attention. The main aim of the present study was to determine the endurance characteristics of hand grip and quadriceps muscles in healthy young adults and then to examine the association between fatigability of the two muscle groups. Methods: Twenty one healthy participants (8 males and 13 females) aged 18-35 years were studied. A maximal intermittent endurance test, consisting of 12 isometric contractions held for 3 seconds separated by 5 second rest periods, was utilised to measure muscle endurance. A Biodex isokinetic dynamometer and Jamar dynamometer were used to assess quadriceps and hand grip respectively. The mean of first (M1) and last (M2) three repetitions was calculated. Fatigue index values were calculated for both muscle groups by the 1st peak torque (PT) minus the last (12th) PT, divided by the 1st PT multiplied by 100. Results: Quadriceps torque (M1:197.3 ± 65.2 Nm; M2:163.1 ± 47.6 Nm) and grip strength (M1:33.6 ± 9.9 Kg; M2:25.2 ± 8.1 Kg) both declined significantly during the 12 repetitions (p < 0.05). Hand grip showed a significantly higher mean fatigue index of 30% compared to 18% in the quadriceps (p < 0.05). Conclusions: Quadriceps showed better fatigability than hand grip. The findings therefore indicate caution against using grip endurance as a surrogate measure of quadriceps endurance. Further research is warranted to confirm observed differences between genders and to study endurance in different age groups.